Assessing the crop water requirements for direct sown Kharif rice in Mirzapur district’s Vindhyan zone, Uttar Pradesh using CROPWAT 8.0 model - SAHU, RADHIKA; MISRA, ANIL KUMAR; SINGH, DHIRENDRA KUMAR; SARANGI, ARJAMADUTTA (Journal of Soil and Water Conservation, 2024)
Efficient water delivery and optimal water utilization are of prime importance in agriculture. Accurate knowledge of crop evapotranspiration (ETc) and crop water requirements (CWR) are crucial for longterm water resource management and the successful conduct of agricultural activities. The present analysis is conducted for direct sown Kharif rice in red sandy loam soil to assess the CWR based on ETc in Mirzapur district, Uttar Pradesh. The CROPWAT 8.0 model was employed to assess the water requirements of rice using 13 years long meteorological data. This involved utilizing daily, decadal and monthly climatic data, along with crop and soil data, applying the FAO Penman-Monteith method. The average annual rainfall for the research area was 944 mm. An average reference crop evapotranspiration (ET0) of 693.88 mm over 13 years (2010-2022) was found and observed to vary from 664.10 to 716.80 mm. The average irrigation requirement for growing kharif rice crops was computed to be 444.04 mm. The highest and lowest crop water requirements were observed as 566.5 mm and 319.4 mm for 2018 and 2021, respectively. FAO experts have endorsed the Penman-Monteith method as the standard for accurate assessments. It involves utilizing it in CROPWAT 8.0 software for computing reference evapotranspiration (ETo) and determining crop water requirements for various crops.